Development of Islamic Character Education Through The Naqsyabandiyah Qadiriyah Order Among The Sasak Wetu Telu Community - Nasihin, Sirajun; Rasyidi, Abdul Haris; Nasri, Ulyan (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aims to analyze the development of Islamic character education through the Naqsyabandiyah Qadiriyah Order among the Sasak Wetu Telu community. As part of the local Islamic tradition, the Wetu Telu community has a unique approach to religious practice and social life. The approach of this order is not only aimed at strengthening spiritual understanding, but also at shaping the moral character of the community through Islamic values, such as honesty, patience, and discipline. The study used a qualitative approach with a field study method involving observation and in-depth interviews with order leaders and the local community. The results of the study indicate that the teachings of the Naqsyabandiyah Qadiriyah Order play a significant role in shaping adaptive Islamic character among the Sasak Wetu Telu such as strengthening Islamic identity, impacts on personal and social life, the role of exemplary tarekat figures, character formation through spiritual discipline, integration of Islam with local culture especially in terms of developing spirituality integrated with local socio-cultural values. These findings confirm that the integration between the order and character education can be a contextual and relevant model of Islamic character development for communities with local Islamic traditions.